SPATIAL VARIATION IN POPULATION CHARACTERISTICS OF VENUS CLAM GAFRARIUM TUMIDUM RÖDING, 1798 (BIVALVIA: VENERIDAE) IN AMBON BAY, MALUKU - Islami, Muhammad Masrur; Bengen, Dietriech Geoffrey; Dody, Safar (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2018)
Ambon Bay consists of two regions i.e. Inner and Outer Ambon Bay that was separated by Galala-Poka sill. Consequently these waters have different local environmental conditions that leads to the bivalve populations differences, one of them is venus clam Gafrarium tumidum. In this study, the distribution and spatial variation in population characteristics of of venus clam was quantified based on the analysis of their twelve shell dimensions from different populations. Fieldwork and analyses were conducted on April – Juni 2013. Total of 585 individuals of venus clam were found and could be divided into ten size-classes and three size categories i.e. small (< 23.11 mm), medium (23.12–32.05 mm) and large size (> 32.06 mm). The highest size-class density was found at medium size. Spatial distribution was related to the characteristics of sediment and other potential factors. Result of discriminant analysis showed that shell-width (SW) was the variable with the highest discriminating power and distinguishing between Inner and Outer Ambon Bay populations.